2006
DOI: 10.1021/la062510y
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Stabilization of Emulsions by a Mixture of Surface-Active Nanoparticles and Surfactant

Abstract: The stability and rheology of tricaprylin oil-in-water emulsions containing a mixture of surface-active hydrophilic silica nanoparticles and pure nonionic surfactant molecules are reported and compared with those of emulsions stabilized by each emulsifier alone. The importance of the preparation protocol is highlighted. Addition of particles to a surfactant-stabilized emulsion results in the appearance of a small population of large drops due to coalescence, possibly by bridging of adsorbed particles. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
178
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(195 citation statements)
references
References 33 publications
13
178
1
Order By: Relevance
“…Such materials provide a new class of supramolecular building blocks and are likely to exhibit unusual, possibly unique properties [14]. So far, the preparation and forming principle of Pickering emulsion have been well documented by Binks and coworkers [15][16][17], Midmore [18], and Bon and coworkers [19,20] Moreover, a series of nanocomposite microspheres have been prepared. Bon and Colver [21] reported the fabrication of a variety of armored latex by Pickering miniemulsion polymerizations using Laponite clay discs as stabilizer.…”
mentioning
confidence: 99%
“…Such materials provide a new class of supramolecular building blocks and are likely to exhibit unusual, possibly unique properties [14]. So far, the preparation and forming principle of Pickering emulsion have been well documented by Binks and coworkers [15][16][17], Midmore [18], and Bon and coworkers [19,20] Moreover, a series of nanocomposite microspheres have been prepared. Bon and Colver [21] reported the fabrication of a variety of armored latex by Pickering miniemulsion polymerizations using Laponite clay discs as stabilizer.…”
mentioning
confidence: 99%
“…Some research groups reported that liquid droplets coalescence or particle detachment was induced when surfactant was added into Pickering emulsions or bubbles due to the adsorption of the surfactant on the particles surface. 26,27 At a high concentration of surfactant, particles were even replaced by surfactant molecules. 28 In our experiments, the surfactant concentration is high (1 wt%).…”
mentioning
confidence: 99%
“…Figure 2 demonstrates the results of the Bapparent viscosity^measurements (defined as the ratio of current stresses to a specified shear rate). As is seen, a pronounced transient (1) or additionally with 0.5 wt.% NaD (2) or MMT (3) process happens reflecting the unlimited increase of apparent viscosity with the tendency to the yield stress, just as was described in [25][26][27].…”
Section: Resultsmentioning
confidence: 52%
“…So-named Pickering emulsions stabilized by solid micro-or nanoparticles were studied in numerous publications [1][2][3][4][5][6][7][8]. Usually the subject of these studies was classical oil-in-water or reverse emulsions.…”
Section: Introductionmentioning
confidence: 99%